2016
DOI: 10.1128/jb.00391-16
|View full text |Cite
|
Sign up to set email alerts
|

Mutagen Synergy: Hypermutability Generated by Specific Pairs of Base Analogs

Abstract: We tested pairwise combinations of classical base analog mutagens in Escherichia coli to study possible mutagen synergies. We examined the cytidine analogs zebularine (ZEB) and 5-azacytidine (5AZ), the adenine analog 2-aminopurine (2AP), and the uridine/thymidine analog 5-bromodeoxyuridine (5BrdU). We detected a striking synergy with the 2AP plus ZEB combination, resulting in hypermutability, a 35-fold increase in mutation frequency (to 53,000 ؋ 10 ؊8 ) in the rpoB gene over that with either mutagen alone. A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Zebularine mutagenicity has not been extensively investigated, except for tests using bacterial cells [56,57]. Zebularine is mainly incorporated instead of cytidine and mispairs with adenine [57].…”
Section: Discussionmentioning
confidence: 99%
“…Zebularine mutagenicity has not been extensively investigated, except for tests using bacterial cells [56,57]. Zebularine is mainly incorporated instead of cytidine and mispairs with adenine [57].…”
Section: Discussionmentioning
confidence: 99%
“…Synergetic responses of biological systems are observed when factors different in their nature act together: gamma-rays and chemical mutagens, heavy metals and radio nuclides, heavy metals and hypothermia, chemical mutagens and ultra-violet rays, laser radiation and magnetic field, etc. (Ang et al, 2016;Song et al, 2016;Kayalvizhi et al, 2017). The existence of a synergetic effect, under the impact of chemical environmental factors, which are particularly seen in small concentrations, was proved on lentils (Lens culinaris Medik.)…”
Section: Tablementioning
confidence: 96%
“…It is important to identify increased mutagenesis that results from combinations of antibiotics and/or chemotherapeutics to allow improved risk assessment in employing these combinations and to possibly uncover new pathways of mutagenesis. In a recent study, we looked for synergies between different base analog mutagens and found a very strong synergy between 2-aminopurine (2AP) and zebularine (ZEB), and a strong antagonistic effect of 2AP on 5-bromodeoxyuridine (5BrdU) (16). We attributed the interaction of base analogs to the resulting changes in the ratios of deoxynucleoside triphosphates (dNTPs) that cause increased mutagenesis, in some cases at specific sequences (16).…”
mentioning
confidence: 99%
“…In a recent study, we looked for synergies between different base analog mutagens and found a very strong synergy between 2-aminopurine (2AP) and zebularine (ZEB), and a strong antagonistic effect of 2AP on 5-bromodeoxyuridine (5BrdU) (16). We attributed the interaction of base analogs to the resulting changes in the ratios of deoxynucleoside triphosphates (dNTPs) that cause increased mutagenesis, in some cases at specific sequences (16). There is extensive literature from studies of both microbial and higher cells showing that alterations of the dNTP pools can affect mutation rates (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
See 1 more Smart Citation